Innovative approaches to the creation of semi-finished meat with the addition of vegetable components - S. Maikova; I. Romashko; O. Masliychuk; O. Vivcharuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології)
The article is devoted to the development of a multicomponent formulation for ready-to-cook meat semi-finished products using plant-based additives such as rosemary extract, kelp powder, and alfalfa. The aim of the study was to enhance the nutritional value, stability, and quality of meat products while reducing dependence on artificial preservatives through the presence of natural antioxidants. The study analyzed the chemical composition of four types of meat raw materials (turkey, rabbit, beef, and beef heart) and the plant components used in the semi-finished products. The research included an analysis of the amino acid and fatty acid composition of the ingredients, which enabled the development of a product formulation balanced in terms of essential amino acids. The high protein content and polyunsaturated fatty acids found in turkey and rabbit meat were taken into account, making these products highly valuable nutritionally. The inclusion of rosemary extract reduced the intensity of oxidative processes, while kelp enriched the product with microelements such as iodine, calcium, and iron. Organoleptic studies revealed that samples containing plant-based additives received the highest ratings for taste, aroma, texture, and appearance. The best results were achieved by a sample containing a combination of rabbit and turkey meat with the addition of rosemary extract, kelp, and alfalfa. The final data confirmed the effectiveness of the proposed formulation, which not only improves the nutritional value of the product but also extends its shelf life without the use of artificial preservatives. The article highlights the potential of using natural plant-based additives in the meat industry to produce products with improved properties that meet modern healthy nutrition standards.